Functional Outcomes After the Surgical Management of Isolated Anterolateral Leg Chronic Exertional Compartment Syndrome. Issue 11 (3rd November 2017) - Gatenby, Grace; Haysom, Samuel; Twaddle, Bruce; Walsh, Stewart
Background: Failure rates of up to 20% have been reported after fasciotomy for chronic exertional compartment syndrome (CECS). There is some evidence that postoperative failure and complication rates are higher in the posterior compartments of the lower leg than the anterolateral compartments. Isolated compartment surgery may put patients at risk of requiring revision surgery because of the risk of developing posterior compartment disease. Hypothesis: Isolated anterolateral fasciotomy for CECS, in the absence of posterior compartment symptoms, produces satisfactory functional outcomes. Study Design: Case series; Level of evidence, 4. Methods: Between 2006 and 2012, patients who had positive intracompartment pressure-testing findings and who underwent isolated anterolateral fasciotomy release for CECS were given a self-administered questionnaire. The minimum follow-up was 3 years. The questionnaire addressed time to return to sport and ongoing symptoms. A visual analog scale was used to assess pain during exercise before and after surgery (score: 0, no pain; 10, worst pain imaginable); overall satisfaction with the procedure was assessed as well. Of 31 eligible patients, 20 patients (36 legs operated on) were assessed. Results: Postoperatively, 90% of participants returned to the same or higher level of sport. The mean pain score during exercise before surgery was 8.17, whereas it was 1.74 after surgery. The overall mean patient satisfaction score was 8.64. Only 1 leg (2.8%) went on to develop posterior compartment syndrome. Conclusion: Isolated anterolateral fasciotomy for CECS produced excellent functional outcomes. Our rate of recurrence was low compared with those found in the literature, and 90% of participants returned to their same or higher level of sport postoperatively.